(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
This study aims to determine the influence of personality traits, based on the theory of the big five personality traits models, towards green purchasing behaviour of young consumers in Sociolla Indonesia with the level of environmental concern as a mediator. The population in this study are consumers of Sociolla Indonesia aged 13-40 years old. This study used nonprobability sampling technique and purposive sampling method. This study used 96 respondents as samples through distributing the questionnaires by Google Form. Data Analysis technique used in Partial Least Square (PLS) with SmartPLS 4.1.0.0 application. The result of this study is from all big five personality traits, neuroticism was the only factor that influenced green purchasing behaviour both directly and indirectly mediated by the level of environmental concern.